DevTMF – Towards code of practice for thermo-mechanical fatigue crack growth. (September 2020) - Stekovic, S.; Jones, J.P.; Engel, B.; Whittaker, M.T.; Norman, V.; Rouse, J.P.; Pattison, S.; Hyde, C.J.; Härnman, P.; Lancaster, R.J.; Leidermark, D.; Moverare, J.
Abstract: The current paper presents work on identification and evaluation of a range of factors influencing accuracy and comparability of data generated by three laboratories carrying out stress-controlled thermo-mechanical fatigue crack growth tests. It addresses crack length measurements, heating methods and temperature measurement techniques. It also provides guidance for pre-cracking and use of different specimen geometries as well as Digital Image Correlation imaging for crack monitoring. The majority of the tests have been carried out on a coarse grain polycrystalline nickel-base superalloy using two phase angles, Out-of-Phase and In-Phase cycles with a triangular waveform and a temperature range of 400–750 °C.